2005
DOI: 10.1111/j.1600-6143.2005.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-donation Assessment of Kidneys by Magnetic Resonance Angiography and Venography: Accuracy and Impact on Outcomes

Abstract: Reports on the accuracy of magnetic resonance angiography (MRA) and magnetic resonance venography (MRV) in evaluating living donor renovasculature employ few patients or omit the consequences of inaccurate scans. We retrospectively compared intraoperative findings to MRA/MRV scans in 146 donorrecipient pairs. For detecting accessory arteries and early branching, MRA sensitivity was 57.6%, specificity 96.5%, false positive rate 3.5%, false negative rate 42.4%, positive predictive value 82.6%, negative predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…reported a series of 146 potential donors investigated with MRA. In their study, MRA detected only 19 of 33 accessory arteries found at transplantation (a sensitivity of 57.6%) and the false positive rate was 3.5% (11). Hodgson et al.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…reported a series of 146 potential donors investigated with MRA. In their study, MRA detected only 19 of 33 accessory arteries found at transplantation (a sensitivity of 57.6%) and the false positive rate was 3.5% (11). Hodgson et al.…”
Section: Discussionmentioning
confidence: 90%
“…However, this technique misses small diameter vessels. Although most missed accessory arteries are inconsequential (11), the importance of preserving lower polar accessory arteries should be considered. MRA has the advantage of avoiding exposure to ionizing radiation therapy, potentially nephrotoxic contrast material and is non‐invasive.…”
Section: Discussionmentioning
confidence: 99%
“…[4589] As CTA is associated with significant amount of radiation, and intravenous contrast administration, several studies evaluated the role of MR in preoperative renal donor evaluation. [678] The NC MRA technique of ASL with 3D SSFP sequence has been evaluated in some recent studies to assess renal vascular anatomy and has produced promising results. [2122] In the current study, we compared Inhance Inflow IR Renal MRA, basically ASL with 3D SSFP sequence and CTA in preoperative renal donors evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The missed renal artery/early branch may increase procedure time and or additional back table procedure with more frequent reconstructed arteries rather than an unacceptable clinical outcome. [6]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation